Penggunaan Software Adobe Animate CC dalam Mendisain Multimedia Interaktif Berbasis Konflik Kognitif pada Gerak Lurus - Shofiah Aini; Fatni Mufit (Postgraduate, University of Mataram, 2022)
The understanding of student concepts found in the field in straight motion materials is still relatively low and the unavailability of teaching materials or multimedia can increase students' understanding of concepts. One solution to be able to solve this problem is to design interactive multimedia based on cognitive conflicts. This study aims to design interactive multimedia based on cognitive conflicts on valid straight-motion materials. Interactive Multimedia based on cognitive conflicts as teaching material to improve understanding of student concepts based on assessments from experts. This research uses a development research method (Design Research) with a group development model. However, the research carried out is limited to the Development or Prototyping phase stage of the expert review section. The object of this study is interactive multimedia based on cognitive conflicts. The data collection instruments in this study are educator questionnaires, journal analysis sheets, and validity test sheets. The data were analyzed using the Percentage technique and the V-Aiken formula. The results of the study obtained interactive multimedia design using Adobe Animate CC software which can be used on student smartphones. This interactive multimedia is compiled based on syntactic cognitive conflict-based learning models. The validity of the product obtained from the assessment of experts obtained the average value of the product, which was 0.81 with a valid category. Interactive multimedia is proven to be valid in terms of material substance, learning design, visual communication display, and use of software